Conservation Strategy in Preserving The Local Image Existence of Wayang Topeng - Suprihatin, Endang Wara; Pratamawati, Dyah (Department of Drama, Dance and Music, FBS, Universitas Negeri Semarang, 2019)
This research studies the strategic conservation efforts to preserve the local image of wayang topeng or mask puppet as a traditional art performance. Ten years into the 21st century shows a great effort from the artists who joined the Wayang Topeng Malang dance studio, Asmorobangun led by Tri Handaya (43), in preserving its existence. This research studies the strategy carried out in preserving the association’s existence so it can continue, not only wayang topeng as traditional art performance but also as the professions of its artist. The efforts carried out shows an action which is systematic and modern. Therefore, the researcher is interested in exploring Tri Handaya’s effort in preserving wayang topeng communities to be able to hold monthly regular performances, establishing cooperation with the government and private sector, and serving various training for general public. Research method used was qualitative approach of single instrumental case study, which is Sanggar Wayang Topeng Asmorobangun. Data was collected with the use of interview, observation, and documentation. Data verification to establish validity was using source and method triangulation. Research results show that there are three strategic aspects in preserving local image: (1) following the tradition patterns of its predecessors, (2) conducting training for young generations, (3) designing an extensive promotional media and building relationships with stakeholders.